2011
DOI: 10.4236/ajac.2011.22025
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Method for the Determination of Total Monosaccharide in <i>Enterobacter cloacae</i> Strains Using Fourier Transform Infrared Spectroscopy

Abstract: Fourier Transform Infrared Spectroscopy (FTIR) was used to quantify total monosaccharide content in the bacterium Enterobacter cloacae and several of its biofilm mutants. Bacterial biofilm samples were grown on trypticase soy agar, and 30 µL aliquots of aqueous sample bacterial plus biofilm were deposited into the center of barium fluoride crystals and dried at 50˚C for 1-hour before being scanned by FTIR. The total amounts of monosaccharides were estimated using the absorbance of the monosaccharide peak, 1192… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Biofilms provide microbes shelter from antimicrobials and the host immune system (Foulquié Moreno et al, 2006 ; Chen and Wen, 2011 ; Rafii, 2015 ; Qi et al, 2016 ; Hall and Mah, 2017 ). Bacterial biofilms have been associated with diseases such as cystic fibrosis, periodontitis, and nosocomial infections on catheters and prosthetic heart valves (Storti et al, 2005 ; Delle Bovi et al, 2011 ). Eradication of biofilms is difficult due to impaired penetration of antibiotics and the decreased host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms provide microbes shelter from antimicrobials and the host immune system (Foulquié Moreno et al, 2006 ; Chen and Wen, 2011 ; Rafii, 2015 ; Qi et al, 2016 ; Hall and Mah, 2017 ). Bacterial biofilms have been associated with diseases such as cystic fibrosis, periodontitis, and nosocomial infections on catheters and prosthetic heart valves (Storti et al, 2005 ; Delle Bovi et al, 2011 ). Eradication of biofilms is difficult due to impaired penetration of antibiotics and the decreased host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms are defined as matrix-enclosed bacterial populations, which adhere to each other and to surfaces; observations have conclusively shown that biofilm bacteria predominate numerically and metabolically, in virtually all ecosystems and are difficult to eliminate [7]. Bacterial biofilms are known to be linked to medical conditions such as cystic fibrosis, periodontitis, and nosocomial infections from the use of catheters and prosthetic heart valves [8]. However, biofilm formation in food processing plants has also been documented; both pathogenic and food spoilage microorganisms have been isolated from such bacterial communities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Infectious caused by microbial communities include urinary tract infections, middle-ear infections, dental plaque, gingivitis, endocarditis, cystic fibrosis. Biofilms on persistent indwelling devices such as catheter, contact lenses, heart valves and joint prostheses are also responsible for many recurrent infections [20,21]. Biofilms on indwelling medical devices may be composed of Gram-positive or Gram-negative bacteria.…”
Section: Bacterial Biofilmsmentioning
confidence: 99%